Probiotic effect of Lactobacillus salivarius C 65 on productive and health indicators of lactating piglets - Rond?n, Ana J.; Ojito, Yuri?n; Arteaga, F?tima G.; Laurencio, Marta; Mili?n, Grethel; P?rez, Y. (Cuban Journal of Agricultural Science, 2013)
For evaluating the probiotic effect of a biopreparation with Lactobacillus salivarius C65 on productive and health indicators in lactating piglets, an experiment was realized with a completely randomized design and two treatments: basic diet (control) and basic diet + C65 biopreparation. Ten piglet litters of the Yorkshire ? Landrace commercial cross x L35 were used from the first day of birth until 35 d of age. As a result from the utilization of this biopreparation, live weight (9.46 kg) of the animals treated with the probiotic improved (P ? 0.05) regarding the control group (8.02 kg) at five weeks. Also there was a better weight increase and daily live weight gain. There was also a decrease in diarrhea incidence. It is confirmed the probiotic potential that this biopreparation has for creating beneficial effects on lactating piglet yield. Key words: probiotic, Lactobacillus salivarius, lactating piglets, nutritional additives